Willing Hands and Hearts: The Rebuilding of the Royal University of Cambodia - Chamnan, Pit (International Higher Education, 2015)
The Royal University of Phnom Penh, formerly Khmer Royal University, was founded in January 1960, with a Faculty of Letters and Humanities and a Faculty of Science and Technology. The language of instruction was French. The university closed in 1975; between 1975 and 1979, under a regime that targeted the educated, most of its faculty were killed. Of those who survived, few remained once the borders opened. Deserted for almost five years, the campus became another victim of the grim civil war.